Comparative study of the corrosion resistance of A95083 in waters of Lake Maracaibo using different electrochemical techniques (Agroindustria, Sociedad y Ambiente, 2018)
Electrochemical techniques, contrary to the gravimetric technique, allow to determine in a fast and reliable way the corrosive behavior of different materials in specific media, for which historically they have been increasingly implemented. However, it is necessary to corroborate the correlation between the values obtained by different techniques in characteristic natural environments, as is the case of Lake Maracaibo due to the existing biodiversity. For this reason, a comparative study was carried out between electrochemical impedance spectroscopy, linear polarization resistance and cyclic polarization, measuring the behavior of the interface resistance of the aluminum alloy A95083, imported and widely used in marine applications. The experimental phase was carried out with a set of tests at the laboratory level, using a conventional electrochemical cell of three electrodes, coupled to a potentiostat. The data processing and its dynamic and systematic analysis and the use of the General Linear Model of ANOVA, allowed to corroborate that there are no significant differences in the values of the interface resistance obtained through the different electrochemical techniques used, which agrees with found in other investigations
Keywords: ANOVA GLM; Aluminum Alloys; Lake of Maracaibo; Interface Resistance